First record of White-Collared Peccary (Dicotyles Tajacu) with Piebaldism across its entire distribution - Otávio Leão-Vulcão; Helena Gurjão Pinheiro do Val; Gabriela Ramos Brasil; Juarez Carlos Brito Pezzuti; Elildo Alves Ribeiro Carvalho Jr (Mammalogy Notes)
Coloration is crucial for mammalian adaptation, influencing predator defense and social behavior. In recent decades, chromatic anomalies have been documented in Neotropical mammals, including albinism, leucism, and piebaldism, affecting several species. Piebaldism is a rare autosomal disorder characterized by asymmetric depigmented patches on the body. This study presents the first record of piebaldism in the collared peccary (Dicotyles tajacu Linnaeus, 1758) throughout its distribution. The record was obtained using camera traps at the Estação Ecológica (ESEC) da Terra do Meio in 2023. Observations showed that the affected peccary coexisted normally with other peccaries and engaged in typical feeding and social behaviors, suggesting that piebaldism does not affect individual social interactions. This finding is consistent with the literature indicating that chemical signals are more important than visual signals in Tayassuidae. This finding highlights the need to understand the frequency and distribution of chromatic anomalies to assess their implications for conservation plans over time.